الضوابط المستحدثة لالستفادة من مزايا وحوافز االستثمار في ظل القانون -22 18 - لزهر لعبيدي (جامعة الوادي University of El Oued, 2024)
Investment serves as a pivotal tool for driving economic development and attracting capital. To ensure its effectiveness, Law No. 22-18 dated July 24, 2022, concerning investment, establishes a legal framework regulating the access to investment incentives and benefits. This law emphasizes setting substantive conditions, including defining eligible activities for incentives and excluding non- priority sectors. It also regulates procedural requirements, such as the registration of investments and the issuance of exploitation permits, thereby enhancing transparency and ensuring the achievement of developmental objectives. This study aims to analyze these updated regulations and assess their anticipated impact on improving the business climate and achieving sustainable development in Algeria. يعد االستثمارأداة محورية لتحقيق التنمية االقتصادية وجذب رؤوس األموال. ولضمان فعاليته، جاء القانون 18-22 املؤرخ في 24 جويلية 2022 واملتعلق باالستثمار، ا ينظم االستفاد من املزايا والحوافز االستثمارية. يركز هذا القانون على وضع شروط موضوعية تشمل تحديد األنشطة املؤهلةلالستفادة من املزايا،واستثناء األنشطة غيرذات األولوية.كما ينظم الشروط اإلجرائيةمثل تسجيل االستثمارات والحصول على محضراالستغالل، ما يعزز الشفافية ويضمن تحقيق األهداف التنموية. تسعى هذه الدراسة إلى تحليل هذه الضوابط املستحدثة، مع استعراض األثر املتوقع لتطبيقها في تحسين مناخ األعمال وتحقيق التنمية املستدامة في الجزائر.
مداخلة في ملتقى وطني